Mycoflora associated with bipolaris leaf blight of different wheat varieties in Bangladesh - Momtaz, Mst Selina; Shamsi, Shamim; Dey, Tapan Kumar (Dhaka University Journal of Biological Sciences, 2019)
Thirty five fungal species, representing 20 genera were found to be associated with Bipolaris leaf blight infected leaves of 21 wheat varieties, collected from eight districts (Dhaka, Gazipur, Dinajpur, Joypurhat, Pabna, Sirajgonj, Kushtia and Chuadanga) of Bangladesh. Fungi were isolated following tissue planting method. The isolated fungi were Alternaria alternata, A. triticina, Arthirinium sp., Aspergillus flavus, A. fumigatus, A. niger, A. terreus, Aspergillus sp., Bipolaris cynodontis, B. oryzae, B. sorokiniana, B. tetramera, B. victoriae, Bispora antenata, Chaetomium globosum, Chaetophoma sp., Cladosporium cladosporioides, Coniothyrium sp., Curvularia affinis, C. lunata, C. pallescens, Drechslera dematioidea, D. hawaiiensis, Epicoccum purpurascens, Eurotium sp., Fusarium moniliforme, F. nivale, F. semitectum, Nigrospora oryzae, N. sacchari, Penicillium digitatum, Pestalotiopsis guepinii, Rhizopus stolonifer, Syncephalastrum racemosum and Trichoderma viride. Bispora antenata is new record for Bangladesh. Dhaka Univ. J. Biol. Sci. 28(1): 21-35, 2019 (January)